The Autobiography Great Kurdish Scholar and Poet (Abdulraheem AL – Mawlawi) and his Method in Proving the Divinity Characteristics - Taher, Naif M. (Humanities Journal of University of Zakho, 2016)
This research highlights the autobiography of the great Kurdish scholar and poet ( Abdulraheem )who is Known by ( AL – Mawlawi) . It also states his method in proving the divinity characteristics , he divided these characteristics into three parts and they are : Psychological feature (Existence) , negative features and meanings features. The research shows that he was full aware of these affairs and it seems that he followed (Al – Ashareya) method. He had refutations about some of the contradictory opinions. The research also shows that he had a wide knowledge in the Islamic legislative science .